2015
DOI: 10.1016/j.exppara.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A non-cytotoxic N-dehydroabietylamine derivative with potent antimalarial activity

Abstract: Malaria caused by the Plasmodium parasites continues to be an enormous global health problem owing to wide spread drug resistance of parasites to many of the available antimalarial drugs. Therefore, development of new classes of antimalarial agents is essential to effectively treat malaria. In this study, the efficacy of naturally occurring diterpenoids, dehydroabietylamine and abietic acid, and their synthetic derivatives was assessed for antimalarial activity. Dehydroabietylamine and its N-trifluoroacetyl, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the other hand, otostegindiol (25, 50, and 100 mg/kg) against Plasmodium berghei exhibited a significant chemosuppression effect (Endale et al, 2013). It should be mentioned that, till date, a number of promising diterpenes and their derivatives have been isolated from natural sources (Pouvelle et al, 1994;Uys et al, 2002;Riel et al, 2002;Kuria et al, 2002;Köhler et al, 2002;Clarkson et al, 2003;Wei et al, 2004;Loyola et al, 2004;Ospina et al, 2005;Kalauni et al, 2006;Ojo-Amaize et al, 2007;Koka et al, 2009;Lane et al, 2009;Wei et al, 2010;Lin et al, 2010;Wangchuk et al, 2010;Stout et al, 2010;Sebisubi et al, 2010;Stout et al, 2011;Cocquyt et al, 2011;Alasbahi and Melzig, 2012;Ebrahimi et al, 2013;Ehrhardt et al, 2013;Walter et al, 2013;Batista et al, 2013;González et al, 2014;Ma et al, 2014;Avilés et al, 2015;Gbedema et al, 2015;Annan et al, 2015;Sadashiva et al, 2015;Namukobe et al, 2015;Ahmad et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, otostegindiol (25, 50, and 100 mg/kg) against Plasmodium berghei exhibited a significant chemosuppression effect (Endale et al, 2013). It should be mentioned that, till date, a number of promising diterpenes and their derivatives have been isolated from natural sources (Pouvelle et al, 1994;Uys et al, 2002;Riel et al, 2002;Kuria et al, 2002;Köhler et al, 2002;Clarkson et al, 2003;Wei et al, 2004;Loyola et al, 2004;Ospina et al, 2005;Kalauni et al, 2006;Ojo-Amaize et al, 2007;Koka et al, 2009;Lane et al, 2009;Wei et al, 2010;Lin et al, 2010;Wangchuk et al, 2010;Stout et al, 2010;Sebisubi et al, 2010;Stout et al, 2011;Cocquyt et al, 2011;Alasbahi and Melzig, 2012;Ebrahimi et al, 2013;Ehrhardt et al, 2013;Walter et al, 2013;Batista et al, 2013;González et al, 2014;Ma et al, 2014;Avilés et al, 2015;Gbedema et al, 2015;Annan et al, 2015;Sadashiva et al, 2015;Namukobe et al, 2015;Ahmad et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] Besides their activities against bacteria and fungi, 1, 1a and their semi-synthetic derivatives also show potential in the fight against malaria and other protozoan diseases. [13][14][15] While 1 itself is not toxic for human cells 14 , several derivatives of 1 and 1a -including some of their amino acid conjugates -exhibit moderate anti-proliferative properties against a panel of tumor cells lines. 16,17 However, their effect on microorganisms has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Hence, development of new, effective antimalarial drugs is urgently needed. Towards this goal, our research group has recently reported the potential utility of 1,2-disubstituted-4-quinolones and abietane diterpenoids as new antimalarial agents, 7,8 and we have been continuing efforts to identify new classes of antimalarial agents.…”
Section: Introductionmentioning
confidence: 99%